Nine Modes of Listening to Music - Santaella, Lucia (Recherches sémiotiques / Semiotic Inquiry, 2017)
Listening has become a major issue of musical composition from the middle of last century on, since Pierre Schaeffer inaugurated with concrete music one of the trends of what would be established under the name of electroacoustic music. The classification of the modes of listening to music that will be presented in this paper is not concerned with the chronological study of listening by means of musical examples from historical periods and their respective social context. As my classification aims at the processes of reception and in a broad sense, I found its foundation in the different interpretative levels formulated by Peirce in his classification of the interpretants.